Assessing the spillover of shocks from the oil market to the stock market of different industry sectors in America - a quantile regression approach - Bakić, Sanja (Serbian Journal of Management, 2024)
The research problem of this paper examines the impact of Brent oil price shocks on stock returns of nine companies from the US market, operating in three different industrial sectors. The observation period covers 2015 to 2023. The research process involves determining the impact of shock transmission using a quantile regression approach. The results show that most of the evaluated quantile parameters are highly statistically significant, i.e. with more than 99% probability. The estimated quantile parameters have the property of being able to observe the spillover effects of shocks in different states of the economy, such as recession, normal state and expansion. The research results suggest that the spillover of shocks from the Brent oil market is most pronounced in the automotive industry sector, that is, in the companies that are most dependent on oil for energy. The significance of the research is reflected in the lack of existing research that deals with the impact of the most important commodity in the world on the prices of company shares with the application of this methodology, which is also a contribution to science. Finally, the results of this research are very relevant for making investment decisions for economic policy makers, investors and company management.